Highly efficient organic photovoltaic devices utilizing work-function tuned graphene oxide derivatives as the anode and cathode charge extraction layers. Issue 5 (12th January 2016) - Konios, Dimitrios; Kakavelakis, George; Petridis, Costantinos; Savva, Kyriaki; Stratakis, Emmanuel; Kymakis, Emmanuel
Abstract : Utilization of work-function (WF) tuned graphene oxide derivatives as cathode and anode buffer layers in organic photovoltaics (OPVs) is demonstrated. Abstract : The effective utilization of work-function (WF) tuned solution processable graphene-based derivatives as both hole and electron transport layers in organic photovoltaic (OPV) devices is demonstrated. The systematic tuning of the functionalized graphene oxide (GO) WF took place by either photochlorination for WF increase, or lithium neutralization for WF decrease. In this way, the WF of the photochlorinated GO layer was perfectly matched with the HOMO level of two different polymer donors, enabling excellent hole transport. Meanwhile the WF of the lithium functionalized GO was perfectly matched with the LUMO level of the fullerene acceptor, enabling excellent electron transport. The utilization of these graphene-based hole and electron transport layers in PTB7:PC71 BM active layer devices led to ∼19% enhancement in the power conversion efficiency (PCE) compared to that of the reference graphene free device, resulting in the highest reported PCE for graphene-based buffer layer OPVs of 9.14%. The proposed techniques open new paths towards novel material and interface engineering approaches for a wide range of new applications, including flexible electronic devices, OPVs, perovskite solar cells, organic light emitting diodes, and photosensors, as well as traditional electronic devices.